A new Canariella species (Gastropoda: Helicoidea: Hygromiidae) of the new subgenus Majorata, both endemic to the Jandía Peninsula (Fuerteventura, Canary Islands) - Alonso, María R.; Ponte-Lira, Carmen E.; Castillo, Carolina; Yanes, Yurena; Groh, Klaus; Ibáñez, Miguel (Zootaxa, 2006)
Canariella jandiaensis sp. nov. and Canariella (Majorata) subgen. nov. are described from the Jandía Peninsula mountains (Fuerteventura Island). The new subgenus, which includes C. jandiaensis and C. eutropis, is characterized mainly by the following synapomorphies: The shell is without hairs and there is a large penial papilla present arising from all the five epiphallar folds. C. jandiaensis differs from C. eutropis in the unkeeled, almost globular shell, which is smaller but taller than that of C. eutropis and has more numerous but smoother radial ribs. Also, C. jandiaensis has a pseudopapilla in the distal penial cavity instead of the thick longitudinal pilaster present in C. eutropis.        The range of Majorata is small, declining from 30,000 years ago and the new species should be classified as “Critically Endangered” based on the very small size of its distribution area (smaller than 1 km2) and the very abundant and free-range livestock present. Mainly goats, grazing freely destroy the habitat in the entire Jandía mountains. Protection of their habitat is recommended, mainly by means of strict livestock control.